Mitotic Activity, Cell Survival, and Neuronal Differentiation in the Hilus of the Dentate Gyrus Under Physiological and Hypothyroid Conditions in Adult Wistar Rats - Karla Sánchez-Huerta; Ana Karen García-Juárez; Lía Diana Colmenero-Rodríguez; Yuliana García-Martínez; Jorge Pacheco-Rosado (Cells)
The adult rodent hippocampus is capable of maintaining its capacity to generate new neurons in the subgranular zone (SGZ) of the dentate gyrus (DG). Interestingly, proliferative cells have also been described in the hilus. The involvement of the hilar neurogenesis process in hippocampal physiology is unknown. Thyroid hormones (THs) are necessary for the survival of postmitotic progenitor cells, neuroblasts, and immature granule neurons in the SGZ. In contrast, evidence concerning the role of THs in the hilar neurogenesis process is limited. The present study characterized the mitotic activity, cell survival, and neuronal differentiation of hilar neurogenesis under physiological and hypothyroid conditions and compared them with those of the granular layer (GL) and the SGZ of the DG in adult Wistar rats. We found that, under physiological conditions, the hilus harbors fewer proliferative cells than the neurogenic zone (GL/SGZ) does, with a rate of cell survival of 18.9% and a rate of differentiation into granular neurons of 19%. Interestingly, hypothyroidism provokes decreased cell proliferation and an increased rate of cell survival without affecting neuronal differentiation. These effects induced by hypothyroidism in the hilus were different or inclusive, contrary to those observed in the neurogenic zone.